A Coupled FEM‐SPH Modeling Technique to Investigate the Contractility of Biohybrid Thin Films. Issue 8 (9th June 2020) - Vannozzi, Lorenzo; Mazzocchi, Tommaso; Hasebe, Arihiro; Takeoka, Shinji; Fujie, Toshinori; Ricotti, Leonardo
Abstract: Biohybrid actuators have the potential to overcome the limitations of traditional actuators employed in robotics, thanks to the unique features of living contractile muscle cells, which can be used to power artificial elements. This paper describes a computational approach for the estimation of the contractile capabilities of skeletal muscle cell‐powered biohybrid actuators based on polymeric thin films. The proposed model grounds on the coupling between finite element modeling and smooth particle hydrodynamics. This allows describing the overall condition, including the viscous forces caused by the surrounding liquid medium, in which biohybrid systems are normally immersed. The model is calibrated by analyzing the contractile behavior of polydimethylsiloxane films coupled with skeletal muscle cells, reported in the literature as muscular thin films. Afterward, it is applied to poly (D, L‐lactic acid) thin films to explore the behavior of these systems, due to myotubes cultured on them, evaluating the role of thickness, tissue maturation status, and hydrostatic pressure on the contractile performance. These results pave the way toward a novel optimization approach of biohybrid robot design relying on the simulation of all the boundary conditions, thus reducing the need for extensive trial‐and‐error efforts. Abstract : A new computational model is proposed, coupling finite element modeling and smooth particle hydrodinamics, to predict the contraction behavior of biohybrid systems. The model is calibrated through state‐of‐the‐art data on muscular thin films and is then applied to analyze the contraction of poly (D, L‐lactic acid) nanofilms. The results pave the way for an optimized design of biohybrid robots .